2019 IEEE Conference on Computational Intelligence in Bioinformatics and Computational Biology (CIBCB) 2019
DOI: 10.1109/cibcb.2019.8791490
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Biological Networks using a Genetic Algorithm with Localized Merge

Abstract: Network graphs appear in a number of important biological data problems, recording information relating to protein-protein interactions, gene regulation, transcription regulation and much more. These graphs are of such a significant size that they are impossible for a human to understand. Furthermore, the ever-expanding quantity of such information means that there are storage issues. To help address these issues, it is common for applications to compress nodes to form supernodes of similarly connected compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For both the unweighted and weighted graphs, we count only the number of edges when determining this distance, not their weights. Previous work [2], [10] identified that in general, lower distances provided better results. The best values for distance are expected to vary from one graph to another.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…For both the unweighted and weighted graphs, we count only the number of edges when determining this distance, not their weights. Previous work [2], [10] identified that in general, lower distances provided better results. The best values for distance are expected to vary from one graph to another.…”
Section: Resultsmentioning
confidence: 90%
“…We consider two fitness functions, both of which are based upon the distortion of the original graph when it undergoes the process of compression followed by decompression; see Section IV-F for full details. It was shown in [10] that for unweighted graphs, when a merge of two nodes requires those nodes to be within a given distance of each other then this tends to lead better fitness; furthermore, it was shown in [2] that this requirement also tends to allow for meaningful interpretation of the underlying data. We explore this concept in the current study for weighted graphs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations